Fertility with artificial insemination: gilts that lock on the insemination spirette vs. those that don't - Schmidt, W.E.; Davis, Duane L.; Stevenson, Jeffrey S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
KSU breeding records show a higher farrowing rate for gilts that "lock" on the insemination spirette at both inseminations as opposed to gilts that "lock" at one insemination or at neither insemination. Continued research is focusing on factors affecting female response to insemination and fertility.
Keywords: Swine; Artificial insemination; Insemination spirette